2022
DOI: 10.1038/s41598-022-10003-7
|View full text |Cite
|
Sign up to set email alerts
|

Hysteretic hERG channel gating current recorded at physiological temperature

Abstract: Cardiac hERG channels comprise at least two subunits, hERG 1a and hERG 1b, and drive cardiac action potential repolarization. hERG 1a subunits contain a cytoplasmic PAS domain that is absent in hERG 1b. The hERG 1a PAS domain regulates voltage sensor domain (VSD) movement, but hERG VSD behavior and its regulation by the hERG 1a PAS domain have not been studied at physiological temperatures. We recorded gating charge from homomeric hERG 1a and heteromeric hERG 1a/1b channels at near physiological temperatures (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…At an experimental level, temperature control can also be an issue, which is important to study ion channel kinetics of temperature-sensitive variants ( Vandenberg et al, 2006 ; Abdelsayed et al, 2015 ; Lei et al, 2019 ; Jones, 2022 ; Ren et al, 2022 ; Kriegeskorte et al, 2023 ). Whilst temperature can be preset on most APC systems (e.g., Biolin Scientific, Fluxion and Nanion Technologies, Table 1 ), most APC assays for cardiac ion channels have been conducted at room temperature ( Vanoye et al, 2018 ; Glazer et al, 2020b ; Ng et al, 2021 ) due to an inherent instability of cell membranes at physiological temperatures leading to lower success rates.…”
Section: Broader Limitations Of Apc Functional Genomics Assaysmentioning
confidence: 99%
“…At an experimental level, temperature control can also be an issue, which is important to study ion channel kinetics of temperature-sensitive variants ( Vandenberg et al, 2006 ; Abdelsayed et al, 2015 ; Lei et al, 2019 ; Jones, 2022 ; Ren et al, 2022 ; Kriegeskorte et al, 2023 ). Whilst temperature can be preset on most APC systems (e.g., Biolin Scientific, Fluxion and Nanion Technologies, Table 1 ), most APC assays for cardiac ion channels have been conducted at room temperature ( Vanoye et al, 2018 ; Glazer et al, 2020b ; Ng et al, 2021 ) due to an inherent instability of cell membranes at physiological temperatures leading to lower success rates.…”
Section: Broader Limitations Of Apc Functional Genomics Assaysmentioning
confidence: 99%
“…[11,12] Previous studies showed homomeric herg1a channel and heteromeric hERG1a/hERG1b channel has distinct effect to drugs and temperature. [13,14] Although the formation of the homomeric and heteromeric hERG1 channels has been shown by various studies, the details of the in vivo oligomerization and stoichiometry are not confirmed and require further investigation. Currently, studies have focused on the relationship between the functionality of the hERG1a channels and the LQTS type 2-associated mutations.…”
Section: Introductionmentioning
confidence: 99%